Significant response of low-dose apatinib monotherapy in brain metastases of triple-negative breast cancer: A case report. Issue 4 (January 2019) - Li, Ting; Wang, Shan-Bing; Lei, Kai-Jian; Jiang, Mao-Qiong; Jia, Yu-Ming
Abstract: Rationale: The potential efficacy of apatinib in patients with advanced triple-negative breast cancer (TNBC) has been observed in a previous phase II clinical study. However, there is no study to evaluate its efficacy and safety in TNBC patients with brain metastasis (BM). Here we report one case that apatinib exhibited excellent antitumor effects in a breast cancer patient with brain metastasis, with no serious treatment-associated with adverse event. Patient concerns: In this case report, one Chinese woman who was diagnosed with stage IV TNBC with multiple bone, lung, and brain metastases was unable to tolerate chemotherapy and refused whole-brain radiation therapy (WBRT) due to her poor physical condition. She had previously undergone radical mastectomy and intravenous chemotherapy. Diagnoses: Triple-negative breast cancer. Interventions: The patient underwent left radical mastectomy with ipsilateral axillary lymph node dissection, and the following adjuvant chemotherapy, but developed multiple bone, lung, and brain metastases. Due to her poor physical condition, chemotherapy was not eligible for her. And she refused WBRT and chose to take low-dose apatinib (250 mg, oral, daily) monotherapy. Outcomes: After 2 months of treatment, the symptom of headache and vomiting relieved and all the brain metastases (BMs) lesions disappeared. Lessons: Low-dose apatinib monotherapy may be an alternative treatment for patients with poor physical condition. Preclinical and clinical studies should be conducted to further evaluate the mechanism and efficacy of apatinib in the treatment of BM from TNBC, as well as to explore the optimal dose of the drug.